2021
DOI: 10.1002/pan3.10218
|View full text |Cite
|
Sign up to set email alerts
|

Urban green space use during a time of stress: A case study during the COVID‐19 pandemic in Brisbane, Australia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
104
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 55 publications
14
104
0
2
Order By: Relevance
“…This suggests that mental health may have improved through the use of UGS, while social health may have been less likely to improve. These results are in common with the findings of the Brisbane study by Berdejo-Espinola et al (2021) [13]. However, Xie (2020) concluded that the users of UGS satisfied their social interaction needs in Chengdu [35].…”
Section: Use Of Ugs During the Pandemicsupporting
confidence: 86%
See 3 more Smart Citations
“…This suggests that mental health may have improved through the use of UGS, while social health may have been less likely to improve. These results are in common with the findings of the Brisbane study by Berdejo-Espinola et al (2021) [13]. However, Xie (2020) concluded that the users of UGS satisfied their social interaction needs in Chengdu [35].…”
Section: Use Of Ugs During the Pandemicsupporting
confidence: 86%
“…The study shows that the frequency of use tended to decrease with age [13]. Xie et al (2020) conducted an online survey of park users in Chengdu, China, from 1 April to 5 April 2020, to analyze the health and well-being benefits of UGS.…”
Section: Previous Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-reported data at various stages of the pandemic has often revealed a decrease in outdoor recreation participation for adults ( Burnett et al, 2021 ; Larson et al, 2021 ; Rice et al, 2020 ; Ugolini et al, 2021 ) and youth ( Jackson et al, 2021 ) across multiple countries. Other studies using self-reported data have found mixed results ( Berdejo-Espinola et al, 2021 ), or even increases in certain regions ( Grima et al, 2020 ; Morse et al, 2020 ). This conflicting evidence, partly an artifact of different contexts and data collection methods ( Labib et al, 2021 ), highlights the need for more research investigating the impact of COVID-19 on outdoor recreation and park use.…”
Section: Introductionmentioning
confidence: 89%